Rekomendasi Prioritas Perbaikan Jalan Dengan Metode AHP-SAW-TOPSIS (Studi Kasus: Dinas Pekerjaan Umum dan Penataan Ruang Kota Malang) - Ayudiya Pramisti Regitha; Nurul Hidayat; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the most important public facilities is roadway as it helps in distributing and delivering various human needs. There are 3776 roadways in Malang, and the total accumulation of its length is 1.221.193 kilometers. Based on the data in 2017, 15% of are damaged. However, the allocation of APBN is very limited, about 3-4%, causing limitation in repairing those damaged roads in the time span of one year. Moreover, that allocation is not enough and so it creates difficulties for the staff of PU Bina Marga to decide the priorities in repairing the damaged roadways as all of them need to be fixed. The solution offered for this problem by creating a program/system that can analyze and make a quick decision about the list of priority in repairing damaged roads which called Sistem Rekomendasi Prioritas Perbaikan Jalan. Criterias used in the decision making of this program are the length of the road, the width of the road, the condition, the acces to certain road, the classification of the road based on its function and the route of public transportation. This system uses MADM Method which consists of AHP, SAW and TOPSIS Method. This research testing has resulted 57,14% .